GRAMD1B is a regulator of lipid homeostasis, autophagic flux and phosphorylated tau - Diana Acosta Ingram; Emir Turkes; Tae Yeon Kim; Sheeny Vo; Nicholas Sweeney; Marie-Amandine Bonte; Ryan Rutherford; Dominic L. Julian; Meixia Pan; Jacob Marsh; Andrea R. Argouarch; Min Wu; et al. (Nature Communications)
Abstract Lipid dyshomeostasis and tau pathology are present in frontotemporal lobar degeneration (FTLD) and Alzheimer’s disease (AD). However, the relationship between lipid dyshomeostasis and tau pathology remains unclear. We report that GRAM Domain Containing 1B (GRAMD1B), a nonvesicular cholesterol transporter, is increased in excitatory neurons of human neural organoids (HNOs) with the MAPT R406W mutation. Human FTLD, AD cases, and PS19 tau mice also have increased GRAMD1B expression. We show that overexpression of GRAMD1B increases levels of free cholesterol, lipid droplets, and impairs autophagy flux. Modulating GRAMD1B in iPSC-derived neurons also alters key autophagy-related components such as PI3K, phospho-AKT, and p62, as well as phosphorylated tau, and CDK5R1. Blocking GRAMD1B function decreases free cholesterol and lipid droplets. Knocking down GRAMD1B additionally reduces phosphorylated tau, and CDK5R1 expression. Our findings elucidate the role of GRAMD1B in the nervous system and highlight its relevance to FTLD and AD.